Kuasa, Tubuh, dan Tanda dalam Meme Politik Pasangan Fiktif Nurhadi-Aldo pada Pilpres 2019 - Yuristia Wira Cholifah; Aditya Eko Adrianto (MediaTor (Jurnal Komunikasi), 2019)
This article discusses how power, body and leftism exist in political memes of NurhadiAldo. Indonesia recently has witnessed the emergence of a pair of fictitious presidential candidates, Nurhadi-Aldo. The pair emerged amid mounting political tension ahead of the Indonesian presidential election for the 2019-2024 period. This fictional couple suddenly became viral with various uploaded memes that seem to be vulgar - related to the body, but some uploads voiced criticism against power. Nurhadi-Aldo, then abbreviated as ‘Dildo’, symbolizes itself as a fake phallus, a fictitious power. This study uses a qualitative method with Peirce’s semiotic approach. Based on the semiotic analysis of Nurhadi-Aldo (NA) meme samples related to power and body, it can be concluded as follows: (1) Political memes can be a medium of aspiration for all parties that are humorous, but effective and viral; (2) The NA Meme comes from two shitposting icons, so NA memes will always cover body, irony, and absurdity; (3) Shitposting which tends to be vulgar and aggressive allows NA meme to bring sensitive topics, especially leftism and body; (4) The appearance of the inverted NA profile photo and the abbreviation attached to them – dildo  has an important role in building a symbol of fictitious power.